Célula de comutação intercalada para conversores com características de seguidor de tensão e comutação suave - Soares, Jefferson Wilhelm Meyer (2021)
This work presents a switching cell with switching frequency modulation (SC-SFM) and continuous conduction in the inductor current. Current-fed converter grounded on SC-SFM have the characteristic of a voltage follower, that is when the input behaves as a resistive load. Simplified control is achieved due to the resistive behavior, only a voltage control loop is needed. Soft switching and current null when the diodes block are reached for a wide power range. In addition, this work presents the operating principle, mathematical analysis, modeling and control scheme for direct current to direct current (DC-DC) converters and power factor correction (PFC) rectifiers, in this case including a feedforward control to improve the power quality. Experimental results are obtained from three prototypes based on SC-SFM. Namely a prototype of interleaved boost converter with switching frequency modulation (IBC-SFM) CC-CC, an IBC-SFM PFC with diode bridge and another IBC-SFM PFC based on the totem-pole structure. The prototypes have a nominal power of 1 kW, an input voltage of 100 V and an output of 240 V for the DC-DC converter and an input voltage of 127 V and an output of 400 V for the PFC converters. Furthermore, the prototypes showed excellent efficiency values with an almost flat curve, with maximum efficiency values equal to 98.78% for the IBC-SFM DC-DC, 97.15% for the IBC-SFM PFC and 97.99% for PFC with totem-pole structure. In the case of PFC converters, the power quality based on power factor (PF), current total harmonic distortion (THD) and harmonic spectrum values present excellent and adequate results for the actual power quality standards.